The role of food and nutrition in the prevention and pathogenesis of chronic kidney disease - Sylwia Wanda Uniejewska (Kazimierz Wielki University, 2019)
The incidence of chronic kidney disease increases with the aging of the population. The occurrence of this disease in our part of the world increases rapidly, which results in increased costs of treatment. Cardiac or renal replacement therapy in the final stages of the disease is very expensive. Keeping patients with CKD (chronic kidney disease) on a proper diet allows for significant improvement of their quality of lives and may extend the moment of introduction of dialysis or the need for a kidney transplant.